2015
DOI: 10.12659/msm.896132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temperature and Stress Distribution on 2 Different Post Systems Using 3-Dimensional Finite Element Analysis

Abstract: BackgroundThe mouth is exposed to thermal irritation from hot and cold food and drinks.Thermal changes in the oral cavity produce expansions and contractions in tooth structures and restorative materials. The aim of this study was to investigate the effect of temperature and stress distribution on 2 different post systems using the 3-dimensional (3D) finite element method.Material/MethodsThe 3D finite element model shows a labio-lingual cross-sectional view of the endodontically treated upper right central inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…21,22,23,24 To examine FEA results on implants, von Mises criteria was chosen to observe the regions with higher stress concentration. 25 To the best of the author's knowledge, there are no studies available in the literature associating implantoplasty and different heights of exposed implants. Although implantoplasty can be considered a rescue treatment for advanced peri-implant lesions, the present study has some limitations: an ideal condition was simulated, excluding the simulation of masticatory loads; the macro-design of the implant used have shorter threads when compared with other designs that present self-tapping threads with more effective cutting flow effect.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,23,24 To examine FEA results on implants, von Mises criteria was chosen to observe the regions with higher stress concentration. 25 To the best of the author's knowledge, there are no studies available in the literature associating implantoplasty and different heights of exposed implants. Although implantoplasty can be considered a rescue treatment for advanced peri-implant lesions, the present study has some limitations: an ideal condition was simulated, excluding the simulation of masticatory loads; the macro-design of the implant used have shorter threads when compared with other designs that present self-tapping threads with more effective cutting flow effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a 3D FEA model of a tooth‐periodontium system with complicated geometry, it is convenient to apply mechanical forces at any regions and in any directions . FEA has provided essential new knowledge for tooth restoration , prosthetic and orthodontic treatment , implant design , tooth fracture and periodontal trauma analysis, as well as the biomechanics of the mandibular system .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to compare the results of this FEA study to the information in the available literature. However, the results of these FEA studies influenced the choice of FRC post in the present study since it was shown that the use FRC posts has a tendency to decrease the stresses in the remaining tooth tissues 10,11,[35][36][37] . Further, as previously mentioned, the beneficial influence of cusp reduction on stress and strain in the dental tissues of endodontically treated premolars was shown in certain FEA studies 13,23) .…”
Section: Discussionmentioning
confidence: 91%
“…Von Mises criterion is a scalar stress measure which combines the three principal stress values and identifies clearly the areas of the model that are under highest stress and are concequently more prone to fatigue failure. It is widely used in FEA studies 44) , including a large number of published studies on the present topic 7,10,11,32,33,36,37) . Hence, the authors have chosen this criterion as to easily compare results with other studies.…”
Section: Discussionmentioning
confidence: 99%